In vivo sensitivity of Phakopsora pachyrhizi to fungicides - Chechi,Amanda (2020)
ABSTRACT: Asian soybean rust is one of the most destructive diseases that can be found in this crop. It can be largely controlled by fungicide application. The objective was to assess the sensitivity of P. pachyrhizi isolates to fungicides. The tests were performed in a completely randomized design, with six replicates. The sensitivity of twelve isolates to site-specific and multisite fungicides at concentrations of 0.1; 1.0; 10.0, and 100.0 mg L-1, plus a control with absence of fungicide (0.0 mg L-1) was assessed. Soybean leaflets were immersed in the appropriate fungicide solutions, disposed in wet chambers in plastic boxes, and inoculated using each uredinia suspension of P. pachyhrizi (5.0 x 104 uredospores mL-1), separately. Boxes were incubated for 20 days at a temperature of 23°C and a 12-hour photoperiod. Next, the number of uredinia per cm2 on the abaxial face of each leaflet was evaluated. The active ingredients prothioconazole, trifloxystrobin, fluxapiroxade, trifloxystrobin + prothioconazole, trifloxystrobin + bixafen + prothioconazole, azoxystrobin + benzovindiflupyr, and azoxystrobin + benzovindiflupyr + diphenoconazole were highly fungitoxic for the majority of the isolates, with EC50 lower than 1.0 mg L-1. Diphenoconazole, azoxystrobin, and fenpropimorph were considered moderately fungitoxic for nine of the twelve isolates, with EC50 between 1 and 10 mg L-1. The multisites mancozeb and copper oxychloride presented EC50 responses classified as low toxic for the twelve isolates and eight for chlorothalonil (EC50 between 10 mg L-1 and 50 mg L-1). Site-specific fungicides showed high-to-moderate fungitoxicity to P. pachyrhizi isolates, even as the multisites presented moderate-to-less toxic activity.